2016
DOI: 10.1080/15438627.2016.1191488
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic, resistance and combined training and detraining on body composition, muscle strength, lipid profile and inflammation in coronary artery disease patients

Abstract: Fifty-six elderly individuals diagnosed with coronary artery disease participated in the study and were divided into four groups: an aerobic exercise group, a resistance exercise group, a combined (aerobic + resistance) exercise group and a control group. The three exercise groups participated in 8 months of exercise training. Before, at 4 and at 8 months of the training period as well as at 1, 2 and 3 months after training cessation, muscle strength was measured and blood samples were collected. The resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 19 publications
4
54
1
6
Order By: Relevance
“…The aerobic exercise stimulus in CEX comprised of 4-min intervals alternately on a cross trainer and cycle ergometer and, therefore, was primarily lower limb aerobic exercise, which itself is a stimulus to improve leg strength. 11,22 In contrast to the effect on lower limb strength in the present study, RES produced greater improvements than CEX in upper limb strength after 12 weeks. This is similar to previous research in healthy older men wherein the training volume of the resistance exercise training group was double that of the concurrent exercise training group.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…The aerobic exercise stimulus in CEX comprised of 4-min intervals alternately on a cross trainer and cycle ergometer and, therefore, was primarily lower limb aerobic exercise, which itself is a stimulus to improve leg strength. 11,22 In contrast to the effect on lower limb strength in the present study, RES produced greater improvements than CEX in upper limb strength after 12 weeks. This is similar to previous research in healthy older men wherein the training volume of the resistance exercise training group was double that of the concurrent exercise training group.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the contribution of the aerobic exercise component to improvements in lower limb strength in the CEX group should not be discounted. The aerobic exercise stimulus in CEX comprised of 4‐min intervals alternately on a cross trainer and cycle ergometer and, therefore, was primarily lower limb aerobic exercise, which itself is a stimulus to improve leg strength …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providers who consider prescribing exercise should know that the risk of experiencing an acute or recurrent MSI will increase with exercise dose, but the risk of experiencing a MSI severe enough to impair daily activities does not increase in dose-response fashion. Muscle strengthening activities may lower the risk of experiencing an MSI during aerobic exercise (Naclerio et al, 2015; Theodorou et al, 2016), perhaps by mediating the inflammatory (C-reactive protein) and muscle damage (creatine kinase and lactate dehydrogenase) responses that occur during and immediately after aerobic exercise (Souglis et al, 2015). Both the ACSM/AHA guidelines (Haskell et al, 2007), and the 2008 Physical Activity Guideline Advisory Committee Report to the Surgeon General (Physical Activity Guidelines Advisory Committee, 2008), concluded that the risks of MSI from exercise are outweighed by the potential health-benefits.…”
Section: Discussionmentioning
confidence: 99%